PENGEMBANGAN MODEL BIMBINGAN KESALEHAN SOSIAL TERHADAP PENALARAN MORAL MAHASISWA JURUSAN BIMBINGAN PENYULUHAN ISLAM - Hamid, Ilham (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam, 2023)
This research aims to: (1) Identify the form of social righteousness guidance model that can enhance the moral reasoning of students from the Faculty of Dakwah and Communication, Department of Islamic Counseling and Guidance at UIN Alauddin Makassar, (2) Determine the validity and practicality of the social righteousness guidance to improve the moral reasoning of students from the Faculty of Dakwah and Communication, Department of Islamic Counseling and Guidance at UIN Alauddin Makassar, and (3) Examine the implementation of an effective social righteousness guidance model to enhance the moral reasoning of students from the Faculty of Dakwah and Communication, Department of Islamic Counseling and Guidance at UIN Alauddin Makassar. This research employs a qualitative design with a grounded theory approach, where the researcher generalizes the observed objects inductively or interacts based on the perspectives of the participating individuals under study. The research was conducted at the Faculty of Dakwah and Communication, Department of Islamic Counseling and Guidance at UIN Alauddin Makassar. The research stages include: (1) Problem formulation stage, (2) Theoretical review stage, (3) Data collection and sampling stage, (4) Data analysis stage, and (5) Conclusion or report writing stage.